The Choice and Partnership Approach to community mental health and addictions services: a realist-informed scoping review protocol - Adrian MacKenzie; Leslie Anne Campbell; Sharon E Clark; Caitlyn Ayn; Jill Chorney; Debbie Emberly; Julie MacDonald; Daniel Marsh; Kylie Peacock; Lori Wozney (BMJ Open, 2019)
Introduction Early identification and appropriate treatment of child and adolescent mental health disorders can often be hampered by patchwork services with poorly planned or unclear pathways. The Choice and Partnership Approach (CAPA) is an evidence-based transformational model of community (community-based or outpatient) mental health and addictions services for children and adolescents that aims to better match services to needs and to improve timely access to care. CAPA has been variably implemented across jurisdictions but has not been comprehensively evaluated for its impact on system and client outcomes. Our research question is, ‘To what degree does CAPA work, for whom and under what circumstances?’. The purpose of this review is twofold: (1) to gain an understanding of the extent and outcomes of the implementation of CAPA in community mental health and addictions services; and (2) to identify the role of context as it influences the implementation of CAPA and resulting client and system outcomes.Methods and analysis We will conduct a realist-informed scoping review of the literature related to CAPA in either child and adolescent or adult community mental health and addictions services. Relevant studies, reports and documentation will be identified by searching the following online databases: MEDLINE, Embase, CINAHL, PsycINFO, Academic Search Premier, ERIC, Web of Science, Cochrane, Dissertations Abstracts, NCBI Bookshelf, PubMed Central and the Canadian Health Research Collection. The search strategy was developed by a health sciences library scientist and informed by a multidisciplinary team comprising methodological and content knowledge experts. The search will gather evidence from multiple online databases of peer-reviewed literature and grey literature repositories. All articles will be independently assessed for inclusion by pairs of reviewers. The key themes derived from a thematic analysis of extracted data will be presented in a narrative overview.Ethics and dissemination Research ethics review is not required for this scoping review. The results will be disseminated through meetings with stakeholders (including clients and families, clinicians and decision-makers), conference presentations and peer-reviewed publication. The results of this review will inform an overarching programme of research, policy and quality indicator development to ultimately improve mental health and addictions care and subsequent mental health outcomes for children and adolescents.